The Effect of The Implementation of E-Filling, E-Billing And Tax Sanctions On The Compliance Of Individual Taxpayers at KPP Pratama Cirebon Dua - Moh. Yudi Mahadianto; Azhaar Kamilia; Ratu Rossa Amelia Ramadhani; Etika Karimatul Fuziani; Nelia Fariani Siregar (Publikasi Indonesia, 2024)
This study aims to examine the influence of the e-filling, e-billing, and tax sanctions systems on the compliance of individual taxpayers. The population in this study is individual taxpayers at KPP Pratam Cirebon Dua. Sampling was carried out using the purposive sampling method. So that the number of samples obtained was 100 respondents. The data analysis technique uses multiple linear analysis with the help of the SPSS 26 program. Before conducting the hypothesis test, a data quality test was carried out which included a validity test and a reliability test, a classical assumption which included a data normality test, a multicollinearity test and a hysteroskedasticity test, then a hypothesis test was carried out through the R2 test, F test and t test. The results of the study show that the implementation of the e-filling system has no effect on taxpayer compliance, while the implementation of the e-billing system and tax sanctions have a positive effect on taxpayer compliance.